Clinical and pathogenetic value of immune disruptions in manifestation of mixed cryoglobulinemia in patients with chronic hepatitis C - O. O. Furyk; Yu. Yu. Riabokon; E. V. Riabokon (Zaporožskij Medicinskij Žurnal)
Objective – to discover role of immune disorders in clinical manifestations formation of mixed cryoglobulinemia in patients with CHC.